1995
DOI: 10.2224/sbp.1995.23.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Socioeconomic Factors as Determinants of Depression Among Puerto Ricans in the United States

Abstract: This paper examines the relationship between degree of acculturation and depression among Puerto Ricans in the United States, controlling for other personal and socio-economic variables. The data analyzed came from the Hispanic Health and Nutrition Examination Survey (HHANES), 198284. For this study a sample of 1,519 of Puerto Ricans 20 years old or older was analyzed using regression (OLS) procedures. The findings of this study did not confirm the assumption that the higher the degree of acculturation among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…In fact, much of the research on the relationship between socioeconomic status and mental health in Latinos reveals poor socioeconomic conditions to be linked to depression (e.g., Canabal & Quiles, 1995;Cuellar & Roberts, 1997). Hence, socioeconomic risk factors are of particular concern for Latinos because many of them migrate to environments that are economically and psychologically challenging (Belitz & Valdez, 1997).…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, much of the research on the relationship between socioeconomic status and mental health in Latinos reveals poor socioeconomic conditions to be linked to depression (e.g., Canabal & Quiles, 1995;Cuellar & Roberts, 1997). Hence, socioeconomic risk factors are of particular concern for Latinos because many of them migrate to environments that are economically and psychologically challenging (Belitz & Valdez, 1997).…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…For instance, Latinos with mental illness may develop an increasing dependency on others (e.g., family members) and experience the worsening of symptoms over time. Also, when Latino families are very cohesive and share much concern for each other, the emotional commitments of being a family member can yield additional stress for the individual experiencing mental health problems (Canabal & Quiles, 1995). Additionally, Latinos whose families are not cohesive may experience stress because their family system is inconsistent with their ideal, well-integrated family system .…”
Section: Cultural Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have suggested that factors such as gender and socioeconomic status significantly influence mental health symptoms more than acculturation alone. Assimilated Mexican Americans reported significantly fewer symptoms of depression compared to their more traditional counterparts (Cuellar & Roberts, 1997;Canabal & Quiles, 1995). It must be noted that these findings are based on a proxy measure of acculturation (e.g., length of stay in U.S. and place of birth).…”
Section: Acculturationmentioning
confidence: 77%
“…Cuellar & Roberts (1997) reported that acculturation did not lessen the increased risk for depression, but economic status associated with ethnicity was found to directly affect depression scores. Similarly, Canabal & Quiles (1995) found that socioeconomic variables such as poverty status and unemployment have a much stronger impact than acculturation on depression symptoms.…”
Section: Socioeconomic Statusmentioning
confidence: 92%